Location of oxygen vacancies in Sr2CuO3+δ single crystal determined by polarized EXAFS at Cu K-edge. (September 2019) - Wang, H.B.; Liang, W.; Luo, Z.L.; Liu, Q.Q.; Huang, H.L.; Yang, M.M.; Yang, Y.J.; Hu, S.X.; Jiang, Z.; Li, S.D.; Sun, X.; Jin, C.Q.; et al.
Abstract: The location of oxygen vacancies in Sr2 CuO3+δ single crystal has been studied by polarized extended x-ray absorption fine structure (PEXAFS) at Cu K -edge. We found that the oxygen vacancies locate both in the CuO2 plane and at the apical site. Among the total 18 ± 8% oxygen vacancies, about 10 ± 5% locates in the CuO2 plane and 8 ± 3% at the apical site. Highlights: The location of oxygen vacancies in Sr2 CuO3+δ single crystal has been studied. We found that the oxygen vacancies locate both in the CuO2 plane and at the apical site. Among the total 18 ± 8% oxygen vacancies, about 10 ± 5% locates in the CuO2 plane and 8 ± 3% at the apical site.